Encyclopedia of cryptography, security and privacy - Jajodia, Sushil; Samarati, Pierangela; Yung, Moti (Springer, 2019)
A rich stream of papers and many good books have been written on cryptography, security, and privacy, but most of them assume a scholarly reader who has the time to start at the beginning and work his way through the entire text. The goal of Encyclopedia of Cryptography, Security, and Privacy, Third Edition is to make important notions of cryptography, security, and privacy accessible to readers who have an interest in a particular concept related to these areas, but who lack the time to study one of the many books in these areas. The third edition is intended as a replacement of Encyclopedia of Cryptography and Security, Second Edition that was edited by Henk van Tilborg and Sushil Jajodia and published by Springer in 2011. The goal of the third edition is to enhance on the earlier edition in several important and interesting ways. First, entries in the second edition have been updated when needed to keep pace with the advancement of state of the art. Second, as noticeable already from the title of the encyclopedia, coverage has been expanded with special emphasis to the area of privacy. Third, considering the fast pace at which information and communication technology is evolving and has evolved drastically since the last edition, entries have been expanded to provide comprehensive view and include coverage of several newer topics. The Encyclopedia will be available as a printed volume when it is finished. In the meantime, it is being made available as an online reference work now; it will be updated regularly as more articles arrive and are finalized for publication.
Keywords: Data structures (Computer science); Data encryption (Computer science); Coding theory; Information theory; Applied mathematics; Engineering mathematics; Computational complexity